Pendalaman Terhadap Masalah Agama, Nilai dan Moral Siswa serta Upaya Penanggulangannya - Asri Atuz Zeky (Indonesian Institute for Counseling, Education and Therapy (IICET), 2014)
This research aim to to get more complete picture at problem of religion, student moral and value and also strive penanggulangannya in SMP Development of UNP. quantitative descriptive Type Research. used by instrument is enquette, documentation study and interview. Amount of sampel 190 people. Data analysed with percentage. Result of Research indicate that problems of ANM at student generally experience of less obedient in running religion, though they thirst for quit ofly is problem of weight which they experience of, they not yet exploited aid service of teacher, specially learn counsellor. Effort learn counsellor to overcome problems of student have optimal enough, but experience of some constraint. This research have [of] implication to counsellor teacher and subject teacher.